The effect of tuberculin skin test and BCG vaccination on the expansion of PPD-specific IFN-gamma producing cells ex vivo. - Ota, M; Brookes, R; Hill, P; Owiafe, P; Ibanga, H; Donkor, S; Awine, T; Mcshane, H; Adegbola, R (2007)
Understanding the immunogenicity of BCG in a population where it has failed will facilitate the design of new TB vaccines. We assessed the immunogenicity of M. bovis BCG over 12 months by ELISPOT assay. Forty-one adolescents and young Gambian male adults received a tuberculin skin test (TST) which was followed one week later by BCG vaccination, but the 23 control subjects received neither of these. TST alone significantly induced PPD-specific IFN-gamma producing cells. Twenty-three percent of subjects did not respond to BCG, which was associated with higher pre-existing ex vivo response to PPD. Paradoxically, amongst BCG responders there was a correlation between pre-existing response and subsequent response to BCG. We conclude that BCG is immunogenic, but this effector response is short-lived and can be limited in higher pre-existing anti-mycobacterial immunity, suggesting a possible threshold beyond which BCG immunogenicity is inhibited.